QUALITY OF SERVICE PADA JARINGAN MULTI PROTOCOL LABEL SWITCHING - Irfan, M.; Syafa'ah, Lailis (Department Industrial Engineering, University of Muhammadiyah Malang, 2009)
MPLS is a work plan that was given by IETF to repair work performance of IP network. Label switching label using forwarding mechanism which has connection oriented characteristic make this technology become routing technology for future guarantec QoS with better service level. This is supporting using a protocol signals for TE-MPLS to maximize network performance balancing the network stressing with distribution that fixed on classes, queuing, and traffic schedule. This research is an analysis of TE-MPLS mechanism to design MPLS network with RSVP-TE daemon that is called emulator MPLS. This analysis used generating 2 different kinds of protocol traffic, UDP, and TCP. The measurement could be concluded that there was an efficiency of MPLS network in group joint of protocol UDP network about 18,6% for channel that is similar with traffic 2 KBRS, 3,4%, 1,5%, and 5,6% for channel similar with traffic 4,8 and 16 KBRS for flow variation of MPLS network data increase 464,2%, 479,5%, 518%, and 2638,5% for each channel. The time that was needed for TCP protocol transmition of MPLS network showed efficiency 2,9% and bit rate of MPLS increase about 0,66%.